Prophetic : An Epistemological Offer for Legal Studies - Kelik Wardiono (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2019)
Purpose of the study:This article aims to define Prophetic (Islamic demystification/Islamic scholarship) which is a concept offered by Kuntowijoyo to integrate science and religion. Unlike western epistemology, prophetic includes revelation and the heart as part of the ontology. From the aspect of prophetic epistemology, it is based on synthetic and analytic approaches with transcendental structural methods, while from axiological aspects, justice with prophetic ethical values are humanization, liberation, and transcendence, becomes the goal and values.Methodology: This research was based on a philosophical approach because it was intended to explore the epistemological building of the prophetic paradigm offered by Kuntowijoyo. The main sources of information in the form of Kuntowijoyo's writings and thoughts about the prophetic paradigm were collected through library studies. The data that have been processed were analyzed using descriptive analysis, interpretation, hermeneutics, and heuristics.Main Findings: Prophetic can be used as one model to integrate science and religion, which is done by connecting the text with the context.Applications of this study: This study can provide keywords that can be used as a guide to understand prophetic such as: (1) qauliyah verses, kauniyah verses, and nafsiyah verses; revelation, reason, heart, and senses, as a keyword in understanding aspects of ontology; (2) synthetic and analytic approaches with transcendental structural methods, as keywords in understanding aspects of epistemology, and; (3) justice which is based on prophetic ethical values encompassing humanization, liberation, and transcendence, as keywords in understanding the axiological aspects.Novelty/Originality of this study: understanding the prophetic paradigm of Kuntowijoyo